A CASE OF MYOCARDIAL INFARCTION IN YOUNG ADULT- HYPERHOMOCYSTENEMIA - DR.M.V.BHARGAVI, M.D; DR.S.SAKTHI SELVA KUMAR M.D; PROF.DR.S.PALANIANDAVAN, M.D; DR. GAMBEER M.D (International Journal of Pharma and Bio Sciences, 2016)
Myocardial infarction is the major complication of coronary artery disease. Recently many studies have proved that hyperhomocysteinemia has a significant role in myocardial infarction. Role of mildly elevated plasma homocysteine as an etiological factor (tHcy) in cardiovascular disease remains undetermined yet it has been proved to be associated with myocardial infarction. Here we present a case of a young male presented as a case of MI who was diagnosed to have hyperhomocysteinemia.